PENGELOLAAN PENGAJARAN KETRAMPILAN KEWIRAUSAHAAN ISLAM DALAM PEMBENTUKAN KEMANDIRIAN SISWA KELAS XI JURUSAN KEUANGAN SMK MUHAMMADIYAH I WEDI KABUPATEN KLATEN TAHUN 2017 - Sukardi, Sukardi (El-Hayah, 2018)
Abstract:Management Skills Entrepreneurship Teaching Islam in Independence Formation Student Class XI Finance Department at SMK Muhammadiyah I Wedi   Klaten  Regency Year 2017. Research formulate how  the management of the Islamic teaching of entrepreneurial skills in the establishment of the independence of class XI students majoring in finance at SMK Muhammadiyah I Wedi Klaten 2017, obstacles and The solution. The research objective 1) describe the management of Islamic teaching of entrepreneurial skills in the establishment  of the independence of class XI students majoring in finance at SMK Muhammadiyah I Wedi Klaten 2017, 2)  to analyze the obstacles and solutions in the development of this research.       The research used qualitative method. The research was conducted at SMK Muhammadiyah I Wedi Klaten from April to June 2017. Subject research subjects. Teacher informants, students, vice principals of the curriculum field, and school supervisors. Data collection technique; interviews, observation and dokumentation.Tehcnic validity of the data using triangulation of data and triaggulasi sumber.  Tecnic data analysis using interactive methods,  data collection, data presentation, data reduction and conclusion.           Results of the study (1) Management of the teaching of entrepreneurial skills in the establishment of the independence of class XI students majoring in finance SMK Muhammadiyah I Wedi Klaten conducted by Planning; Entrepreneurship enters the curriculum on the subject, the practice of each skill program. Graduates are able to create their own jobs. Organizing: principals, committees, teachers,  students,  supervisors and education offices. Implementation;  Entrepreneurial skills are taught;  Buying and selling,  convection, garment, small business, home industry and others. Supervision  is done on schedule once a month on all series of school  activities, student circumstances,  facilities,  teachers,  programs,  facilities.  Evaluation; Every one month after the supervision of  Dikdasmen,  principals,  school committees, teachers, school superintendents.  Obstacles;  Limited  time allocation, parental dependence, lack of interest and talent  of students,  there has been no cooperation of others.  Solutions;  Widespread  time  allocation,  according  to  student interest talents, good oversight. Entrepreneurship  skills education communities and educational institutions,  students  spirit  of  independence,  honesty,  sincerity, tenacity,  awoke  and  formed in self student.Cooperation with other parties. Keywords: Management, Skill, entrepreneurship and independence.